Burning Bright: Essays in Honour of David Bindman - Murdoch, Tessa (UCL Press, 2015)
This book celebrates the work and career of the internationally renowned art historian, David Bindman, on the occasion of his 75th birthday, and is above all a tribute to him from his former students and colleagues. With essays on sculpture, drawings, watercolours and prints, the volume reflects the extraordinary range of Bindman's knowledge of works of art and his impact through his teaching and research on the understanding of British and European artistic developments from the eighteenth to the twentieth century. The essays cast light on questions of technique and stylistic change, patronage, collecting and iconography, and engage with issues such as the representation of race, gender, sexuality, political violence and propaganda, exile, and notions of the canon. The artists discussed here include Hogarth, Blake, Roubiliac, Thorvaldsen and Canova, all subjects of books by David Bindman, as well as Morland, Rowlandson, Gillray, Millais, Munch, Nevinson, and Heartfield.